Investigating Computational Thinking in K–12 Visual Programming Activities on Code.org: A Brennan-Resnick Framework Approach - Cucuk Wawan Budiyanto; Kristof Fenyvesi; Yustika Indah Maharani; Rosihan Ari Yuana; Putri Khoirin Nashiroh; Rizka Latifah (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2025)
Global interest in Computational Thinking and learning to code has increased. Teaching elementary school students to code and develop computational thinking is a crucial skill for the 21st century. Code.org or Scratch are increasingly used by researchers and educators to evaluate the best practices in digital environment. Such an understanding leads to the urgency to investigate how the block-based programming environment contributes to the development of Computational Thinking and how the development takes place for K-12 students. This research departed from the previous study on the use of Brennan and Resnick framework to evaluate the development of Computational Thinking in various literature on visual programming. Employed a qualitative design, the research investigates K-12 students' response to the activity. The portfolio, then, analyzed using the Brennan and Resnick Framework for Computational Thinking development. The results demonstrated that six of the seven computational concepts could be taught in 10 stages using the “Dance Party” task. Work on the animation project in the tenth stage of “Dance Party” has well-prepared the four computational practices projects. This has a great deal to do with the student's ability to question perspective, as young people do not perceive a disconnect between the surrounding technology and their ability to negotiate reality.